PENGARUH LIVE STREAMING SHOPEE TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF KONSUMEN GENERASI Z - MOCHAMMAD RIFNI BAYU SATRIAWAN; Tyan Yoga Ramadhanu; Tan Evan Tandiyono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to examine the effect of Shopee Live on the impulse buying behavior of Generation Z consumers. A qualitative descriptive approach was employed through semi-structured, in-depth interviews with four Generation Z informants selected using purposive sampling. Data were analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. The findings reveal that Shopee Live significantly influences impulse buying behavior through promotional strategies such as flash sales, limited-time discounts, and free shipping offers. In addition, social interaction, live product demonstrations, audience testimonials, and emotional engagement during live streaming increase consumers' purchase intentions. The study also found that Fear of Missing Out (FOMO) reinforces consumers' tendency to make spontaneous purchasing decisions. These findings contribute to the understanding of consumer behavior in live-streaming commerce and provide practical implications for digital marketing strategies.